Harvesting energy from planetary gear using piezoelectric material - Chilabi H.J.; Salleh H.; Supeni E.E.; As'arry A.B.; Md Rezali K.A.; Atrah A.B. (MDPI AG, 2023)
Energy harvesting; Frequency converters; Piezoelectric materials; Piezoelectricity; Energy Harvester; Interchangable planet cover; Piezoelectric; Planetary Gears; Rotational energy; Speed